On the Nature of Everyday Prospection: A Review and Theoretical Integration of Research on Mind-Wandering, Future Thinking, and Prospective Memory. Issue 3 (September 2020) - Kvavilashvili, Lia; Rummel, Jan
The ability to imagine and simulate events that may happen in the future has been studied in several related but independent research areas (e.g., episodic future thinking, mind-wandering, prospective memory), with a newly emerging field of involuntary future thinking focusing primarily on the spontaneous occurrence of such thoughts. In this article, we review evidence from these diverse fields to address important questions about why do people think about the future, what are the typical and most frequent contents of such thoughts, and how do these thoughts occur (are they spontaneous or constructed deliberately). Results of the literature review provide support for the pragmatic theory of prospection, by showing that when people engage in prospective thought naturally, without being explicitly instructed to do so, they predominantly think about their upcoming tasks and planned activities instead of simulating plausible but novel hypothetical scenarios. Moreover, prospective thoughts are more often spontaneous than deliberate and effortful, and their occurrence seems to increase the likelihood of planned activities being completed in the future. The findings are discussed in the context of a new "pragmatic dual process account" of future thinking, and new avenues for future research on prospection are outlined.